Further Advances in Cancer Immunotherapy: Going Beyond Checkpoint Blockade - Wilkinson, Robert W.; Leishman, Andrew J. (Frontiers in Immunology, 2018)
Significant advances have been made to identify effective therapies that either restore or generate de novo a patient’s immune response to cancer, so called immunotherapy or immuno-oncology (IO) therapies. Some tumours overcome immune surveillance by promoting mechanisms to evade or suppress the immune system. This conference report highlights the clinical promise and current challenges of IO therapy, including the use of immune-checkpoint antagonist monoclonal antibodies (mAbs). Further the report investigates advances in preclinical modelling of cancer immuno-biology and how this is helping our understanding of which patients will receive clinical benefits from current immune-checkpoint treatment. Looking to the future, the report looks at emerging IO approaches, which aim to specifically target the tumour microenvironment (TME). This includes the use of TOLL-like receptors (TLRs) agonists which link the activation of innate immune cells to the priming of T cells and an adaptive memory anti-tumour immune response, through to the reversal of local immune-suppression using adenosinergic and indoleamine 2,3-dioxygenase (IDO) inhibitors.